Audit Quality, Delay, SIZE, and ROA’s Impact on PBV in IDX FnB - Sianipar, Dame Rosa; Tania, Maybelline; Astuty, Fuji; Hayati, Keumala (Economics and Business Solutions Journal, 2025)
This study investigates the influence of Audit Quality, Audit Delay, Firm Size (SIZE), and Return on Assets (ROA) on firm value, proxied by Price to Book Value (PBV), in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2024 period. The research focuses on 25 companies, with data obtained from their published financial statements. The analytical method applied is multiple linear regression, supported by hypothesis testing through the F-test and t-test. Prior to the regression analysis, classical assumption tests were conducted to ensure the reliability and validity of the model. The empirical results reveal that Audit Quality, Firm Size, and ROA do not have a statistically significant effect on PBV. However, Audit Delay is found to exert a significant negative influence, suggesting that longer delays in audit completion reduce firm value as perceived by investors. When tested simultaneously, the four independent variables fail to show a significant predictive power in explaining PBV variations. This finding is further confirmed by the Adjusted R Square value of 0.037, indicating that only 3.7% of the variation in firm value can be explained by the studied variables, while the remaining 96.3% is likely influenced by other factors outside the scope of this model. Overall, the study concludes that among the examined determinants, only Audit Delay significantly affects firm value in IDX-listed food and beverage companies, while Audit Quality, Firm Size, and ROA do not exhibit notable contributions. The limited explanatory power of the model highlights the need for future research to incorporate additional financial and non-financial factors that may better capture the dynamics of firm value.
Keywords: Audit Quality; Audit Delay; Firm Size; ROA; PBV